2016
DOI: 10.1002/smll.201502666
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Beam Pen Lithography

Abstract: Beam pen lithography (BPL) in the liquid phase is evaluated. The effect of tip-substrate gap and aperture size on patterning performance is systematically investigated. As a proof-of-concept experiment, nanoarrays of nucleotides are synthesized using BPL in an organic medium, pointing toward the potential of using liquid phase BPL to perform localized photochemical reactions that require a liquid medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Wu et al also demonstrated a V-shaped PDMS tip coated with a thin film of metal for large-area sub-wavelength nanopatterning [ 174 ] as well as fabricating nanopatterns using the aperture existing at the oblique sidewalls of PDMS relief structures [ 175 ]. BPL is also used in a liquid form to synthesize nucleotides [ 176 ]. Liquid-phase BPL provides a way to perform local photochemical reactions that requires a liquid medium.…”
Section: Advancement Of Scalable Tbn Approachesmentioning
confidence: 99%
“…Wu et al also demonstrated a V-shaped PDMS tip coated with a thin film of metal for large-area sub-wavelength nanopatterning [ 174 ] as well as fabricating nanopatterns using the aperture existing at the oblique sidewalls of PDMS relief structures [ 175 ]. BPL is also used in a liquid form to synthesize nucleotides [ 176 ]. Liquid-phase BPL provides a way to perform local photochemical reactions that requires a liquid medium.…”
Section: Advancement Of Scalable Tbn Approachesmentioning
confidence: 99%
“…Each tip actually acts like a near-field scanning optical microscopy (NSOM) tip, resulting in feature sizes below the diffraction limit of the employed UV light source. Relevant applications of this method were demonstrated in the field of photochemical reactions for nucleotide synthesis, 31 metal oxide synthesis 32 and nanoscale confined oxidation reactions, 33 but the use of BPL is not directly applicable for printing delicate biomolecules at high resolution due to the need for UV light to trigger the patterning process.…”
Section: Caterina Alfanomentioning
confidence: 99%
“…Nevertheless, trade-offs are inevitable among cost, throughput, flexible feature size, and geometry, , and a cost-effective photolithographic strategy to produce submicron patterns with flexible feature geometries over a large area remains elusive . Recently, the development of polymer pen lithography, beam pen lithography (BPL), and related techniques has enabled nanopatterns over a large range of the nanoscale. ,,− However, it is challenging to apply BPL to the fabrication of TFTs or FETs because this requires an opaque metal for the coating and subsequent creation of subwavelength nanoscopic apertures at the apexes of metal-coated elastomeric pyramids, , and the repeated friction between metal-coated tips and substrates gradually wears off the metal coating …”
mentioning
confidence: 99%